Cardiovascular and cerebrovascular responses to cardio‐respiratory events in preterm infants during the transitional period. (23rd July 2020) - Martini, Silvia; Frabboni, Giulia; Rucci, Paola; Czosnyka, Marek; Smielewski, Peter; Galletti, Silvia; Cimatti, Anna Giulia; Faldella, Giacomo; Corvaglia, Luigi; Austin, Topun
Abstract : Key points: Non‐invasive simultaneous multiparametric monitoring allows the in vivo evaluation of cerebral and cardiovascular haemodynamic responses to different types of recurrent episodes of intermittent hypoxia and/or bradycardia, also defined as cardio‐respiratory events (CRE), in preterm neonates during postnatal transition. By decreasing left cardiac output, bradycardia further contributes to cerebral hypoxia during CRE. The presence of a haemodynamically significant patent ductus arteriosus results in a deeper impairment of cerebral oxygen status in response to CRE, whereas the brain‐sparing remodelling of the fetal circulation resulting from placental insufficiency is associated with more favourable haemodynamic responses to intermittent hypoxia. During transition, the haemodynamic impact of CRE is influenced not only by the event type, but also by specific clinical features; this highlights the importance of developing individualized approaches to reduce the hypoxic burden in this delicate phase. Abstract: The present observational prospective study aimed to investigate cerebral and cardiovascular haemodynamic responses to different types of cardio‐respiratory events (CRE) in preterm infants during postnatal transition, as well as evaluate the impact of relevant clinical characteristics. Infants with gestational age (GA) <32 weeks and/or birth weight <1500 g were enrolled after birth. Cerebral oxygenation index (cTOI), fractional oxygen extraction (cFTOE), cardiac output (CO), cardiac contractility (iCON) and systemic vascular resistances (sVR) were simultaneously monitored over the first 72 h by near‐infrared spectroscopy and electrical velocimetry. CRE were clustered into isolated bradycardia (IB), isolated desaturation (ID) and combined desaturation/bradycardia (DB). For each parameter, percentage changes from baseline (%Δ) were calculated. The impact of different CRE types and clinical variables on %Δ was evaluated with generalized estimating equations. In total, 1426 events were analysed. %ΔcTOI significantly differed among ID, IB and DB ( P  < 0.001), with the latter showing the greatest drop. %ΔcFTOE decreased significantly during DB ( P  < 0.001) and ID ( P  < 0.001) compared to IB. DB and IB were associated with more negative %ΔCO ( P  < 0.001) and more positive %ΔsVR ( P  < 0.001) compared to ID. A slight iCON reduction was observed during DB compared to ID ( P  = 0.043). Antenatal umbilical Doppler impairment, GA and the presence of a haemodynamically significant patent ductus arteriosus had a significant independent impact on %ΔcTOI, %ΔcFTOE and %ΔCO. During the transitional period, the haemodynamic responses to CRE are influenced by the event type and by specific neonatal characteristics, suggesting the importance of targeted individualized approaches for minimizing the risk of cerebral injury in the preterm population. Key points: Non‐invasive simultaneous multiparametric monitoring allows the in vivo evaluation of cerebral and cardiovascular haemodynamic responses to different types of recurrent episodes of intermittent hypoxia and/or bradycardia, also defined as cardio‐respiratory events (CRE), in preterm neonates during postnatal transition. By decreasing left cardiac output, bradycardia further contributes to cerebral hypoxia during CRE. The presence of a haemodynamically significant patent ductus arteriosus results in a deeper impairment of cerebral oxygen status in response to CRE, whereas the brain‐sparing remodelling of the fetal circulation resulting from placental insufficiency is associated with more favourable haemodynamic responses to intermittent hypoxia. During transition, the haemodynamic impact of CRE is influenced not only by the event type, but also by specific clinical features; this highlights the importance of developing individualized approaches to reduce the hypoxic burden in this delicate phase.